2018
DOI: 10.1186/s12886-018-0892-1
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glaucoma secondary to bilateral idiopathic dilated episcleral veins – a case report

Abstract: BackgroundIdiopathic elevated episcleral venous pressure (IEEVP) or idiopathic dilated episcleral veins (IDEV) is a rare abnormality, and thus therapeutic treatment for this condition rarely is discussed. We report a case of a patient with bilateral glaucoma secondary to IDEV for whom intraocular pressures (IOPs) were controlled successfully by trabeculectomy.Case presentationA 50 year-old female with a complaint of persistent red eyes for over 30 years, presented with numerous tortuous and engorged episcleral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…IEEVP or Radius-Maumenee syndrome is characterized by arterialized, engorged, and tortuous episcleral veins, with raised IOP, and, almost always, open-angle glaucoma is already present at the time of diagnosis [ 3 , 6 , 7 , 13 ]. It affects individuals of any age with no gender preference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IEEVP or Radius-Maumenee syndrome is characterized by arterialized, engorged, and tortuous episcleral veins, with raised IOP, and, almost always, open-angle glaucoma is already present at the time of diagnosis [ 3 , 6 , 7 , 13 ]. It affects individuals of any age with no gender preference.…”
Section: Discussionmentioning
confidence: 99%
“…It affects individuals of any age with no gender preference. This condition could be unilateral or bilateral; when bilateral, it may be asymmetrical [ 3 ]. IEEVP is a diagnosis of exclusion and can only be established after other conditions, some of which are life-threatening, have been excluded [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it would be prudent to keep in mind the cause-effect relationship of episcleral venous congestion. Literature has numerous reports of bilateral idiopathic dilated episcleral venous congestion leading to bilateral glaucoma 5 , 6 , 7 as well as unilateral idiopathic dilated episcleral venous congestion leading to ipsilateral glaucoma. 8 , 9 Groh MJ et al 10 even reported a case of the Radius-Maumenee syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is AH fluid and ion exchange in cornea, iris and vitreoretinal interface, no significant net fluid movement is found. In the trabecular pathway, also known as the direct or conventional outflow pathway, AH flows through the multilayered TM and the inner wall of SC into the lumen of SC, where it will pass through collector channels and reenter systemic circulation via the episcleral venous plexus and the aqueous veins of Ascher [30] (Figure 2). AH in the uveoscleral pathway, also known as the indirect or unconventional outflow pathway, is taken up by the iris root and flows through the uveal meshwork, the anterior face of ciliary muscle and the connective tissues between the muscle bundles.…”
Section: Ah Outflowmentioning
confidence: 99%